Решить уравнение; х²-43=0 1-(2-3х)=3(5-2х)

Dan4ik1111111111 Dan4ik1111111111    3   24.09.2019 07:00    3

Ответы
илья1947 илья1947  10.09.2020 15:49
Решение смотри на фотографии
Решить уравнение; х²-43=0 1-(2-3х)=3(5-2х)
ПОКАЗАТЬ ОТВЕТЫ
Ludmila28041985 Ludmila28041985  10.09.2020 15:49
Х² - 43 = 0
х² = 43+0
х² = 43
х(1) = √43;
х(2) = – √43.

1 - ( 2 - 3х) = 3( 5 - 2х )
1 - 2 + 3х = 15 - 6х
- 1 + 3х = 15 - 6х
3х + 6х = 15 + 1
9х = 16
х = 16 ÷ 9
х = 16/9
х = 1 ( целая ) 7/9
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра